Epidemiology, risk factors, and association of antifungal prophylaxis on early invasive fungal infection in heart transplant recipients. Issue 5 (9th September 2021) - Yetmar, Zachary A.; Lahr, Brian; Brumble, Lisa; Gea Banacloche, Juan; Steidley, D. Eric; Kushwaha, Sudhir; Beam, Elena
Abstract: Background: Invasive fungal infection (IFI) in heart transplant recipients is associated with poor outcomes. Estimated risk of 1‐year IFI in heart transplant recipients is 3.4–8.6% with risk factors inconsistently identified in previous studies. The role of antifungal prophylaxis is unclear. The transplant program at Mayo Clinic provides 6 months of universal azole prophylaxis for those heart transplant recipients in Arizona. We sought to define risk factors for 1‐year IFI and determine the effect of antifungal prophylaxis. Methods: We conducted a retrospective cohort study of patients undergoing heart transplantation at Mayo Clinic from January 2000 to March 2019. We analyzed demographics, details of transplant hospitalization, antifungal prophylaxis, and fungal infection. Multivariable Cox analyses were performed to identify risk factors of 1‐year IFI and impact of IFI on posttransplant mortality. Results: A total of 966 heart transplant recipients were identified with a median age of 56 years (IQR 47, 62). A total of 444 patients received antifungal prophylaxis. Over 1‐year follow‐up, 62 patients developed IFI with a cumulative incidence of 6.4%. In multivariable analysis, factors associated with IFI were renal replacement therapy (RRT) (HR 3.24, 95% CI 1.65–6.39), allograft rejection (HR 2.33, 95% CI 1.25–4.34), and antifungal prophylaxis (HR 0.32, 95% CI 0.11–0.96). RRT was also associated with invasive mold infection (HR 3.00, 95% CI 1.29–6.97). Conclusions: RRT and allograft rejection after transplantation are associated with 1‐year IFI, and RRT is also associated with invasive mold infection. Antifungal prophylaxis appears to be protective and further study is needed in the heart transplant population.